2018
DOI: 10.1128/aem.02335-17
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome Structure Influences Infection by the Parasite Crithidia bombi in Bumble Bees

Abstract: Recent declines in bumble bee populations are of great concern, and have prompted critical evaluations of the role of pathogen introductions and host resistance in bee health. One factor that may influence host resilience when facing infection is the gut microbiota. Previous experiments with , a European bumble bee, showed that the gut microbiota can protect against, a widespread trypanosomatid parasite of bumble bees. However, the particular characteristics of the microbiome responsible for this protective ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
105
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(138 citation statements)
references
References 65 publications
(84 reference statements)
13
105
3
Order By: Relevance
“…Further studies with field caught bees showed a negative correlation between Crithidia bombi infection and the presence of a betaproteobacterial symbiont Snodgrassella (Koch & Schmid‐Hempel, ). Additionally, recent results from Bombus impatiens studies indicate that a higher microbiome diversity, high bacteria abundance and the presence of Gilliamella , Lactobacillus Firm‐5 and Apibacter core gut bacteria are associated with low Crithidia bombi infection titres (Mockler et al., ). In other Bombus species, infection with Crithidia is negatively associated with the abundance of Gilliamella symbiont and positively associated with the abundance of noncore bacterial symbionts (Cariveau, Powell, Koch, Winfree, & Moran, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies with field caught bees showed a negative correlation between Crithidia bombi infection and the presence of a betaproteobacterial symbiont Snodgrassella (Koch & Schmid‐Hempel, ). Additionally, recent results from Bombus impatiens studies indicate that a higher microbiome diversity, high bacteria abundance and the presence of Gilliamella , Lactobacillus Firm‐5 and Apibacter core gut bacteria are associated with low Crithidia bombi infection titres (Mockler et al., ). In other Bombus species, infection with Crithidia is negatively associated with the abundance of Gilliamella symbiont and positively associated with the abundance of noncore bacterial symbionts (Cariveau, Powell, Koch, Winfree, & Moran, ).…”
Section: Discussionmentioning
confidence: 99%
“…Such interactions coupled with the experimental and/or genetic tractability of some insect–microbe associations provide a prospective application of symbionts in disease control strategies (Beard et al., ). Despite the huge number of insect taxa associated with monoxenous trypanosomatids and gut microbiota (Engel & Moran, ; Kaufer et al., ; Maslov et al., ; Schaub, ), the dynamics and outcomes of host–symbiont–parasite interactions have only been reported in a few taxa such as bumblebees (Koch & Schmid‐Hempel, ; Mockler, Kwong, Moran, & Koch, ) and honeybees (Schwarz, Moran, & Evans, ). The study of monoxenous parasites, which has enhanced our understanding of the biology and evolution of their dixenous counterparts (Flegontov et al., ), and the ability of these parasites to complete their life cycle in a single host makes them attractive for use in experimental manipulations.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in honey bees, the same Snodgrassella alvi pre‐treatment that resulted in high gut bacterial abundance and proliferation of Gilliamella apicola (Orbaceae) also led to higher levels of infection with the trypanosomatid L. passim (Schwarz et al ., ). Although previous studies with bumble bees have implicated Gilliamella‐ rich microbiota in resistance to C. bombi infection (Koch and Schmid‐Hempel, ; Mockler et al ., ), the Orbaceae clade is phenotypically diverse, varying in traits such as carbohydrate metabolism and resistance to antimicrobial peptides despite conserved 16S rRNA gene sequences (Engel et al ., ; Kwong et al ., ), and may harbour strains associated with both health and disease. For example, a cross‐colony survey correlated high levels of Gilliamella (‘Gamma‐1’) with honey bee colony collapse (Cox‐Foster et al ., ), intensity of infection with the honey bee‐infective microsporidian Nosema ceranae (Rubanov et al ., ), and general ‘dysbiosis’ associated with low adult bee mass, high mortality, the scab‐forming bacterium Frischella perrara , and Nosema infection (Maes et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Both results suggest that the infection treatment provoked an immune response that enhanced resistance to colonization by noncore symbionts. Previous research in bumble bees has documented effects of the microbiota on trypanosomatids (Koch and Schmid-Hempel, 2011;Mockler et al, 2018), but not of exposure to C. bombi on either beneficial or pathogenic bacteria. However, C. bombi inoculation can cause an immune response that resembles the reaction to injection with heat-killed bacteria, characterized by production of antimicrobial peptides, other antibacterial effector proteins and reactive oxygen species Brunner et al, 2013).…”
Section: High Temperature and Trypanosomatid Exposure Conferred Protementioning
confidence: 98%
“…A landmark study by Koch and Schmid‐Hempel () found that sterile B. terrestris (bumble bees) inoculated with fresh faeces from hive mates had significantly lower levels of infection by the parasite Crithidia bombi when compared to their counterparts fed sterile syrup, demonstrating the influence of the microbiome on host health. Using faecal transplants, it was shown that this protective ability varies with microbiota composition and parasite strain (Koch and Schmid‐Hempel, ; Mockler et al ., ) and that the mechanism behind this may be the microbial pH alteration of the gut environment (Palmer‐Young et al ., , pre‐print).…”
Section: Functional Contributions To the Honey Bee Hostmentioning
confidence: 99%